Assessment of fun from the analysis of facial images - Vieira, Luiz Carlos (2017)
This work investigates the feasibility of assessing fun from only the computational analysis of facial images captured from low-cost webcams. The study and development was based on a set of videos recorded from the faces of voluntary participants as they played three different popular independent games (horror, action/platform and puzzle). The participants also self-reported on their levels of frustration, immersion and fun in a discrete range [0,4], and answered the reputed Game Experience Questionnaire (GEQ). The faces were found on the videos collected by a face tracking system, developed with existing implementations of the Viola-Jones algorithm for face detection and a variation of the Active Appearance Model (AAM) algorithm for tracking the facial landmarks. Fun was represented in terms of the prototypic emotions and the levels of frustration and immersion. The prototypic emotions were detected with a Support Vector Machine (SVM) trained from existing datasets, and the frustration, immersion and fun levels were detected with a Structured Perceptron trained from the collected data and the self reported levels of each affect, as well as estimations of the gradient of the distance between the face and the camera and the blink rate measured in blinks per minute. The evaluation was supported by a comparison of the self-reported levels of each affect and the answers to GEQ, and performed with measurements of precision and recall obtained in cross-validation tests. The frustration classifier could not obtain a precision above chance, mainly because the collected data didn\'t have enough variability in the reported levels of this affect. The immersion classifier obtained better precision particularly when trained with the estimated blink rate, with a median value of 0.42 and an Interquartile Range (IQR) varying from 0.12 to 0.73. The fun classifier, trained with the detected prototypic emotions and the reported levels of frustration and immersion, obtained the best precision scores, with a median of 0.58 and IQR varying from 0.28 to 0.84. All classifiers suffered from low recall, what was caused by difficulties in the tracking of landmarks and the fact that the emotion classifier was unbalanced due to existing datasets having more samples of neutral and happiness expressions. Nonetheless, a strong indication of the feasibility of assessing fun from recorded videos is in the pattern of variation of the levels predicted. Apart from the frustration classifier, the immersion and the fun classifier were able to predict the increases and decreases of the respective affect levels with an average error margin close to 1.